Connectedness between energy and nonenergy commodity markets: Evidence from quantile coherency networks - Rabeh Khalfaoui; Eduard Baumöhl; Suleman Sarwar; Tomáš Výrost (ZBW - Leibniz Information Centre for Economics, 2021)
The worldwide economy has experienced several changes in energy and nonenergy prices. This has motivated academics, investors, and policymakers to analyze the relationships between energy and nonenergy commodity markets. In this study, a novel approach of quantile coherency is used to examine the dependence structure between energy and nonenergy commodity pairs at different frequencies and quantiles in their joint return distribution over the period 1960:M1–2019:M10. Overall, the empirical findings illustrate evidence of low significant dependency between energy and nonenergy commodity markets across different frequencies and quantiles. In addition, our findings show that some nonenergy commodity markets have a neutral relationship with global energy commodity markets.
Keywords: Q1; Q4; Q02; P28; 330; Energy; Nonenergy; Quantile coherency; Network analysis; Dependence; Commodity markets